2021
DOI: 10.1371/journal.pone.0251595
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged ex-vivo normothermic kidney perfusion: The impact of perfusate composition

Abstract: Normothermic machine perfusion (NMP) of donor kidneys provides the opportunity for improved graft preservation and objective pre-transplant ex-vivo organ assessment. Currently, a multitude of perfusion solutions exist for renal NMP. This study aimed to evaluate four different perfusion solutions side-by-side and determine the influence of different perfusate compositions on measured renal perfusion parameters. Porcine kidneys and blood were obtained from a slaughterhouse. Kidneys underwent NMP at 37°C for 7 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Few studies to date have conducted head-to-head comparisons of perfusates for EVNP. A recent publication from Pool et al, however, compared four different perfusates during 7-hour EVNP of porcine kidney in a DCD model ( 36 ). While all four perfusates demonstrated feasibility, there were apparent differences between electrolyte levels, renal function parameters, and injury markers in the four groups.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies to date have conducted head-to-head comparisons of perfusates for EVNP. A recent publication from Pool et al, however, compared four different perfusates during 7-hour EVNP of porcine kidney in a DCD model ( 36 ). While all four perfusates demonstrated feasibility, there were apparent differences between electrolyte levels, renal function parameters, and injury markers in the four groups.…”
Section: Discussionmentioning
confidence: 99%
“…The machine perfusion setup was similar to previously described setups by our group. 18 , 19 The perfusion circuit consisted of a pump unit and centrifugal pump (cirQlife, XVIVO, Göteborg, Sweden), oxygenator (Hilite 800 LT, Medos Medizintechnik AG), LifePort organ chamber (Organ Recovery Systems), and thermal unit (Kidney Assist, XVIVO, Göteborg, Sweden). Pressure was measured at the distal end of the straight cannula (TruWave disposable pressure transducer, Edwards Lifesciences, Irvine, CA), flow was monitored using an ultrasonic clamp-on flow probe (Transonic Systems Europe B.V., Elsloo, the Netherlands), and temperature was monitored using a temperature sensor (Heraeus Nexensos PT100 Surface Sensor [W-SZK], Heraeus Nexensos GmbH, Kleinostheim, Germany), which was positioned underneath the kidney close to the venous outflow.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, proteomics analysis showed decreased damage-associated molecular patterns, angiotensinogen levels, and enhanced levels of enzymes involved in kidney metabolism, perfused with urine recirculation (81). Pool et al recently demonstrated that perfusate composition also significantly impact kidney injury and perfusion parameters during prolonged NMP (83). Basile et al observed stable perfusion parameters and no evidence of damage during 72 h of NMP, revealing that even several days of perfusion could be feasible (79).…”
Section: Normothermic Machine Perfusionmentioning
confidence: 99%